Exploring the Relationship between Financial and Macroeconomic Factors with Manufacturing Stock Prices - Faizul Mubarok; Erliana Indasaputry; Shofia Shofia; Aulia Sepviani (Jurnal Akuntansi Indonesia, 2024)
ABSTRACTStock is a promising investment option for investors, encouraging the need for an in-depth understanding of the impact of internal and external factors on share price movements. This research aims to analyze the influence of liquidity, profitability, inflation, and exchange rates on stock prices in the manufacturing sector. With a quantitative approach, the research uses secondary data. It applies a purposive sampling method to select a sample of manufacturing companies that meet the criteria for being listed companies on the Indonesia Stock Exchange during the 2018-2023 period by applying the Fixed Effect Model. The analysis was carried out using the Fixed Effect Model (FEM) in selecting the best model where FEM takes into account time-invariant heterogeneity across companies, effectively controlling for unobserved variables that differ between companies but remain constant over time. The research results show that profitability and inflation have a significant influence on stock price movements, while liquidity and exchange rates do not have a significant influence. The implications of these findings provide a deeper look into the factors influencing share prices in the manufacturing sector, contributing to a better understanding of investment decision-making.